New Developments in Anterior Laryngeal Recording Technique During Neuromonitored Thyroid and Parathyroid Surgery - Liu, Cheng-Hsin; Huang, Tzu-Yen; Wu, Che-Wei; Wang, Jia Joanna; Wang, Ling-Feng; Chan, Leong-Perng; Dionigi, Gianlorenzo; Chiang, Feng-Yu; Tseng, Hsin-Yi; Lin, Yi-Chu (Frontiers in Endocrinology, 2021)
A recurrent laryngeal nerve (RLN) injury resulting in vocal fold paralysis and dysphonia remains a major source of morbidity after thyroid and parathyroid surgeries. Intraoperative neural monitoring (IONM) is increasingly accepted as an adjunct to the standard practice of visual RLN identification. Endotracheal tube (ET) surface recording electrode systems are now widely used for IONM; however, the major limitation of the clinical use of ET-based surface electrodes is the need to maintain constant contact between the electrodes and vocal folds during surgery to obtain a high-quality recording. An ET that is malpositioned during intubation or displaced during surgical manipulation can cause a false decrease or loss of electromyography (EMG) signal. Since it may be difficult to distinguish from an EMG change caused by a true RLN injury, a false loss or decrease in EMG signal may contribute to inappropriate surgical decision making. Therefore, researchers have investigated alternative electrode systems that circumvent common causes of poor accuracy in ET-based neuromonitoring. Recent experimental and clinical studies have confirmed the hypothesis that needle or adhesive surface recording electrodes attached to the thyroid cartilage (transcartilage and percutaneous recording) or attached to the overlying neck skin (transcutaneous recording) can provide functionality similar to that of ET-based electrodes, and these recording methods enable access to the EMG response of the vocalis muscle that originates from the inner surface of the thyroid cartilage. Studies also indicate that, during surgical manipulation of the trachea, transcartilage, percutaneous, and transcutaneous anterior laryngeal (AL) recording electrodes could be more stable than ET-based surface electrodes and could be equally accurate in depicting RLN stress during IONM. These findings show that these AL electrodes have potential applications in future designs of recording electrodes and support the use of IONM as a high-quality quantitative tool in thyroid and parathyroid surgery. This article reviews the major recent developments of newly emerging transcartilage, percutaneous, and transcutaneous AL recording techniques used in IONM and evaluates their contribution to improved voice outcomes in modern thyroid surgery.